EFL STUDENTS’ EXPERIENCES OF USING QUILLBOT FOR PARAPHRASING IN THESIS WRITING - Anggun Hasanah Dwi Andina; Ahmad Ridha; Hidayati Hidayati (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
Thesis writing requires students to engage with scholarly sources and paraphrase them accurately while preserving the original meaning. To support this process, AI-assisted writing tools such as QuillBot have become increasingly popular among EFL students. However, the value of these tools depends on how students use them in academic writing. Participants were selected through a preliminary questionnaire and data were collected via semi-structured interviews with three English Education students. Selected thesis excerpts were also comparatively analyzed across the original source text, the QuillBot-generated paraphrase, and the participants' final revision to trace how AI-generated output was modified before incorporation, while interview data were analyzed thematically. The findings show that participants integrated QuillBot into their writing process while recognizing its limitations: rather than accepting AI-generated paraphrases directly, they compared them with the original source, critically evaluated their accuracy, and reconstructed them before use. Documentary evidence confirmed that final texts consistently differed from QuillBot's output, indicating participants treated it as an initial draft rather than a final product. The study concludes that QuillBot functioned as a learning support tool rather than a writing substitute, underscoring the importance of critical AI literacy in academic writing.